Study Analysis of Serum Phosphorylated Tau (P-Tau) Levels with Severity and Outcome in Traumatic Brain Injury Patients: A Single Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Istiqomah; Syafrita, Yuliarni; Fanny Adhy Putri; Syarif Indra; Restu Susanti; Reno Bestari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Traumatic brain injury (TBI) is a global health problem that can cause death and disability in people of productive age. The diagnosis and assessment of TBI severity currently still rely on clinical examination and neuroimaging. However, limited access and cost of neuroimaging are obstacles in many health facilities. Therefore, blood-based biomarkers are needed that can help the diagnosis and prognosis of TBI. Phosphorylated Tau (p-tau) is a potential biomarker that can be measured in serum. This study aims to assess the relationship between serum p-tau levels and severity and outcome in TBI patients. Methods: This research is a comparative study with a cross-sectional design involving 70 TBI patients who came to the emergency room (ER) of Dr. M. Djamil General Hospital Padang. TBI severity was assessed using the Glasgow coma scale (GCS) and grouped into mild (GCS 13-15) and moderate to severe (GCS 3-12). Outcomes were assessed using the Glasgow outcome scale (GOS) and grouped into good (GOS 4-5) and poor (GOS 1-3). Serum p-tau levels were measured using the ELISA method. Data analysis was carried out using SPSS. Results: The median serum p-tau level in the mild TBI group was 165.84 ng/L (IQR 126.18-463.85), while in the moderate to severe TBI group, it was 177.68 ng/L (IQR 87.62-591 .93). There was a significant difference between serum p-tau levels in the mild and moderate to severe TBI groups (p=0.029). The median serum p-tau level in the good outcome group was 167.21 ng/L (IQR 87.62-463.85), while in the poor outcome group it was 187.04 ng/L (IQR 137.75-591.93). There was a significant difference between serum p-tau levels in the good and bad outcome groups (p=0.014). Conclusion: Serum p-tau levels have a significant relationship with severity and outcome in TBI patients. Elevated serum p-tau levels are associated with increased severity of TBI and poor outcomes. Further research is needed to confirm these findings and explore the potential of p-tau as a biomarker in TBI management.